Has the Fed Responded to House and Stock Prices? A Time-Varying Analysis - Knut Are Aastveit; Francesco Furlanetto; Francesca Loria (Norges Bank, 2017)
In this paper we use a structural VAR model with time-varying parameters and stochastic volatility to investigate whether the Federal Reserve has responded systematically to asset prices and whether this response has changed over time. To recover the systematic component of monetary policy, we interpret the interest rate equation in the VAR as an extended monetary policy rule responding to inflation, the output gap, house prices and stock prices. We find some time variation in the coefficients for house prices and stock prices but fairly stable coefficients over time for inflation and the output gap. Our results indicate that the systematic component of monetary policy in the US i) attached a positive weight to real house price growth but lowered it prior to the crisis and eventually raised it again and ii) only episodically took real stock price growth into account.
hdl:11250/2495598
Keywords: C32; E44; E52; E58; 330; Bayesian VAR; time-varying parameters; monetary policy; house prices; stock market